Hanging out in the city of tomorrow: a participatory approach to researching the importance of music and the arts in the lifeworlds of young people. (2nd July 2020) - Stehlik, Tom; Carter, Jenni; Price, Deborah; Comber, Barbara
ABSTRACT: The satellite city of Elizabeth, located 30 km north of South Australia's capital Adelaide, was established in the 1950s as an experiment in urban sociological planning, populated with new arrivals and hailed as the 'City of Tomorrow'. By the 1970s, it had declined into one of the most disadvantaged communities in South Australia, with intergenerational unemployment, poverty and social dysfunction leading to disengagement and disenfranchisement of the current generation of young people living there. In 2007 the local council developed a community facility to attract young people into creative learning and expression through music and the performing arts. This was the council's response to its shared responsibility for caring for the young people in its community and their personal, social and educational wellbeing. 'Northern Sound System' offers programs and resources for contemporary music composing, recording and performance. This article reports on the affordances of applying a youth participatory inquiry approach in a study in Elizabeth, to establish young people's views on music and the creative arts in relation to their lifeworlds, in particular their interests, personal wellbeing and social interactions. Most young people reported music played a large part in maintaining a positive outlook. However, there were differences in how young men and women talked about the creative arts in their lives, which may have implications for the provision of programs and safe spaces for young people to 'hang out' and engage in creative pursuits.